Influence of Cutting Parameters and MQL on Surface Finish and Work Hardening of Inconel 617 - Rachel Lai; Andres Hurtado Carreon; Jose M. DePaiva; Stephen C. Veldhuis (Applied Sciences)
Inconel 617 is a nickel-based superalloy that is a primary candidate for use in next-generation nuclear applications such as the Gen IV Molten Salt Reactor (MSR) and Very-High-Temperature Reactor (VHTR) due to its corrosion and oxidation resistance and high strength in elevated temperatures. However, Inconel 617 machinability is poor due to its hardness and tendency to work harden during manufacturing. While the machinability of its sister grade, Inconel 718, has been widely studied and understood due to its applications in aerospace, there is a lack of knowledge regarding the behaviour of Inconel 617 in machining. To address this gap, this paper investigates the influence of cutting parameters in the turning of Inconel 617 and compares the impact of Minimum Quantity Lubrication (MQL) turning against conventional coolant. This investigation was performed through three distinct studies: Study A compared the performance of commercial coatings, Study B investigated the influence of cutting parameters on the surface finish, and Study C compared the performance of MQL to flood coolant. This work demonstrated that AlTiN coatings performed the best and doubled the tool life of a standard tungsten carbide insert compared to its uncoated form. Additionally, the feed rate had the largest impact on the surface roughness, especially at high feeds, with the best surface quality found at the lowest feed rate of 0.075 mm/rev. The utilization of MQL had mixed results compared to a conventional flood coolant in the machining of Inconel 617. Surface finish was improved as high as 47% under MQL conditions compared to the flood coolant; however, work hardening at the surface was also shown to increase by 10–20%. Understanding this, it is possible that MQL can completely remove the need for a conventional coolant in the machining of Inconel 617 components for the manufacturing of next-generation reactors.